(untitled) (Research, Society and Development, 2022)
The present study aims to investigate the profile of the leader in people management in modern companies in the face of changes in a generic way in the world and a marked impact on the business world. The development of the study is justified by the fact that it can show a society that, in globalized times, computerized processes and intense competition, as companies came to need even more efficient management systems and competent leadership, in order to develop the best of its teams and competences and provide products and services with better quality and faster delivery. In terms of applied research methodology, this is a literature review that aims to address and present the thoughts of the authors consulted on the topic proposed in the study and then reach the objectives proposed in this study. It was concluded that the leader must have a motivating profile, showing individual conduct and enthusiasm and thus become a symbol of conduct, in addition to approaching employees in particular, with a pattern of dispersing an excitement. Therefore, the leader needs to seek success to create a sense of improvement throughout the change.